Effects of perinatal variables on echocardiographic assessments of left ventricular dimensions in infants born large for gestational age: a prospective cohort analysis - Ahmed Amarah (17733726) (2025)
Background To assess the relationship between perinatal factors, and echocardiographic left ventricular (LV) dimensions after delivery in infants who are large for gestational age (LGA). Methods This prospective cohort study that was conducted between 2014 and 2018, and involved healthy LGA newborns born ≥ 35 weeks’ gestation, delivered at New York-Presbyterian Brooklyn Methodist Hospital, and a control group of appropriate for gestational age (AGA) infants. Data were analyzed using multivariate linear regression in STATA. Results A total of 563 neonates were enrolled in this study. They were composed of 414 AGA infants as the control group and 149 LGA infants as the intervention group. Males were predominant in both groups. A larger proportion of neonates were admitted to the neonatal intensive care unit (NICU) in LGA infants (74.6%) as compared to the AGA infants (33.5%) (p < 0.001). Regression analysis identified birth weight (BW) as a key factor, positively correlating with increased LVmass, interventricular septum thickness, and LV posterior wall thickness in both LGA and AGA infants. Additionally, BW showed a positive correlation with left ventricular internal dimensions in diastole and systole. Higher maternal BMI was associated with an increase in fractional shortening in LGA infants, while maternal insulin use during pregnancy was positively associated with interventricular septum thickness. Notably, male infants exhibited significantly higher LV internal dimensions in both diastole and systole, while GA negatively impacted the left ventricular mass index. Conclusion The study's findings underscore the significant influence of perinatal factors on neonatal cardiac morphology in both LGA and AGA infants. Certain perinatal variables were identified as key determinants affecting various aspects of LV structure. These insights highlight the importance of considering these perinatal factors in neonatal cardiac assessments for early detection and intervention. Other Information Published in: Italian Journal of Pediatrics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s13052-025-01945-5